Social Simulation of Intergroup Conflicts Using a New Model of Opinion Dynamics - Ishii, Akira; Okano, Nozomi; Nishikawa, Masaru (Frontiers in Physics, 2021)
In this article, a social simulation is conducted using opinion dynamics theory that includes trust and distrust among and between two in-group members. In particular, we simulated social conflicts in the United States society on gun control, gay marriage, abortion, immigration, racial equality, health insurance, legalization of marijuana, and belief in a conspiracy theory. From the calculation of the opinion dynamics, the division becomes serious when the divided and polarized societies reach a consensus with trust to the opposite. On the contrary, even if it is polarized, if a trust is not robust and cannot form a consensus, it is suggested that the division is not severe from the calculation of opinion dynamics.